The Influence of Female Leadership Towards Performance: Evidence from Western European Financial Firms - Cong-Duc Tran; Ly Pham T. Minh; Jo-Yu Wang (International Journal of Business and Society, 2021)
Does the appearance of women at the executive position in the boardroom make any differences in firm performance, especially in the financial sector which is well-known to be a male dominated sector? Inspired by that question, our study aims to explore the influence of female leadership in firm performance. We investigate this relationship from a comprehensive dataset comprising of 310 listed financial institutions from 21 Western European countries. The endogeneity concerns were removed using a Two stage approach least square (2SLS) and Generalized method of moments (GMM). Critically, we demonstrated that women’s appearance at alternative managerial levels, including the chairperson, executive, and total female directors in the boardroom, negatively influences both firm accounting and market-based performance. We further explore that the percentage of women in the boardroom (excepting non-executive female directors) has a negative impact on performance only in low-performing firms. Our findings argue with previous studies which encouraged more involvement of women at higher managerial levels. We believe that women’s unique characteristics are addressed to alleviate interest behavior, but they tend to reduce the performance of financial firms.